CIVIL-PATRIOTIC VALUES IN THE SYSTEM OF VALUE ORIENTATIONS SOLDIERS - A. Kravets (Вестник университета, 2019)
The article deals with the results of empirical studies of semantic determination of civil-patriotic price-servicemen of the Russian Interior Troops with deep structured interview.